Centaurium erythraea extract reduces redox imbalance and improves insulin expression and secretion in pancreatic β-cells exposed to oxidative and nitrosative stress - Đorđević, Miloš; Grdović, Nevena; Mihailović, Mirjana; Arambašić Jovanović, Jelena; Uskoković, Aleksandra; Rajić, Jovana; Đorđević, Marija; Tolić, Anja; Mišić, Danijela; Šiler, Branislav; Poznanović, Goran; Vidaković, Melita; et al. (Archives of Biological Sciences, 2020)
Paper description: Oxidative stress underlies b-cell damage and a diminished capacity for insulin secretion in diabetes. Previously we have shown that the Centaurium erythraea extract (CEe) exhibits a significant redox potential both in vitroand in an animal model of diabetes. Herein we examined the antioxidant effects of CEe in H2O2-and sodium nitroprusside (SNP)-treated Rin-5F b-cells. CEe attenuated the H2O2- and SNP-induced redox imbalance, contributing to a decrease in DNA, lipid and protein damage and to an increase in cell-viability and insulin expression and secretion. Abstract: Oxidative stress is one of the major mechanisms that underlies the damage of pancreatic b-cells and defects in insulin secretion in diabetes. As herbal preparations can alleviate oxidative stress through their redox-active secondary metabolites, in this study we investigated the cytoprotective effects of Centaurium erythraea extract (CEe) against H2O2- and SNP-induced oxidative/nitrosative stress in Rin-5F b-cells. The antioxidant activity of CEe and its effect on cell survival and insulin expression/secretion were evaluated. The CEe increased cell viability and ameliorated the disturbance of redox homeostasis in H2O2- and SNP-treated cells by decreasing DNA damage, lipid peroxidation and protein S-glutathionylation. The CEe restored GSH homeostasis in H2O2-treated b-cells and attenuated the SNP-induced disturbance of the GSH/GSSG ratio. The H2O2- and SNP-induced disruption of CAT, GPx, GR, MnSOD and CuZnSOD activities was adjusted by the CEe towards control values, as well as mRNA and protein levels of GPx, MnSOD and CAT. The CEe increased insulin expression/secretion particularly in H2O2-treated b-cells, which was in accordance with the more pronounced antioxidant effect of the CEe observed in H2O2-treated b-cells as compared to SNP-treated cells. These findings support the beneficial effect of the CEe in preventing or slowing down b-cell damage and dysfunction caused by oxidative/nitrosative stress during diabetes development. https://doi.org/10.2298/ABS200127005D Received: January 27, 2020; Revised: January 31, 2020; Accepted: January 31, 2020; Published online: February 10, 2020 How to cite this article: Đorđević M, Grdović N, Mihailović M, Arambašić Jovanović J, Uskoković A, Rajić J, Đorđević M, Tolić A, Mišić D, Šiler B, Poznanović G, Vidaković M, Dinić S. Centaurium erythraea extract reduces redox imbalance and improves insulin expression and secretion in pancreatic β-cells exposed to oxidative and nitrosative stress. Arch Biol Sci. 2020;72(1):117-28.